TOWARDS SHAPING PUPILS’ SOFT-SKILLS: THE ISLAMIC TEACHING AT A BILINGUAL SCHOOL IN BANDA ACEH - Emawati Emawati; Rahmatun Nisa; Teuku Zulfikar (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2020)
The Indonesian educational system should guarantee that educational institutions in all levels not only train their students’ cognitive ability but also develop their affective domain. This important domain can be developed through various strategies, one of which is through shaping students’ soft-skills. This classroom research was conducted to identify strategies implemented by a particular bilingual school in Banda Aceh, in its attempt to develop students’ soft-skills. Having interviewed four teachers and the school principal, observed classroom, and analyzed documents, such as learning module and syllabus, we found that the teachers use various strategies in developing students’ soft-skills, one of which is through inviting students to participate in learning process and to engage in outdoor activities; promoting democratic dialogues; showing empathy and appreciation, and also presenting good examples are seen as important strategies to develop soft-skills.